Peran manajerial dosen dalam meningkatkan mutu pelayanan akademik di Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) - Hurriyah, ’Aisyah Indana Zulfa Al Hurriyah Sasa (Maliki Interdisciplinary Journal, 2025)
This study discusses the managerial role of lecturers in improving the quality of academic services at State Islamic Higher Education Institutions (PTKIN). Lecturers not only function as teachers, but also as planners, organizers, implementers, and evaluators of various academic activities that determine the quality of educational services. Through good managerial skills, lecturers are able to develop structured learning plans, manage classes effectively, maintain coordination with various academic units, and conduct continuous evaluations of the learning process. These roles contribute significantly to creating professional, responsive academic services that are oriented towards student needs. This study confirms that improving the managerial capacity of lecturers is a strategic step for PTKIN in strengthening a culture of quality, increasing student satisfaction, and promoting a more competitive and competitive quality of Islamic higher education. Therefore, collaboration between institutions, lecturers, and the government is needed to ensure that the managerial role of lecturers can be carried out optimally.